2010
DOI: 10.1007/s11689-010-9046-3
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory processing in neurodevelopmental disorders

Abstract: The purpose of this article is to review the role of somatosensory perception in typical development, its aberration in a range of neurodevelopmental disorders, and the potential relations between tactile processing abnormalities and central features of each disorder such as motor, communication, and social development. Neurodevelopmental disorders that represent a range of symptoms and etiologies, and for which multiple peer-reviewed articles on somatosensory differences have been published, were chosen to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(159 citation statements)
references
References 90 publications
1
142
0
6
Order By: Relevance
“…On the other hand, the somatosensory cortex has been implicated in the processing of social cues to motivation, emotion, and cognition, which finally links to social behaviors in human beings. Somatosensory processing impairment is found in a range of neurodevelopmental disorders including ASD and is associated with deficits in communication, motor ability, and social skills in these disorders (9). In animal studies, Tabuchi et al (10) showed that ASD-relevant neuroligin-3 mutation (R451C) knock-in mice exhibited a behavioral phenotype composed of social interaction deficits, increased spatial memory, and increased inhibitory synaptic transmission in the somatosensory cortex.…”
mentioning
confidence: 99%
“…On the other hand, the somatosensory cortex has been implicated in the processing of social cues to motivation, emotion, and cognition, which finally links to social behaviors in human beings. Somatosensory processing impairment is found in a range of neurodevelopmental disorders including ASD and is associated with deficits in communication, motor ability, and social skills in these disorders (9). In animal studies, Tabuchi et al (10) showed that ASD-relevant neuroligin-3 mutation (R451C) knock-in mice exhibited a behavioral phenotype composed of social interaction deficits, increased spatial memory, and increased inhibitory synaptic transmission in the somatosensory cortex.…”
mentioning
confidence: 99%
“…Touch is the primary sense through which we express intimate emotions [21]. It is vitally important for the proper development of infants [81], and is a social adhesive that binds together those in a romantic relationship [170]. Touch has played a central role in history [101] and between different cultures its role is diverse [363].…”
Section: The Importance Of Social Touchmentioning
confidence: 99%
“…Given the importance of touch in the early stages of life in mammals, the lack of touch (i.e. tactile deprivation) may indeed have had a profound negative impact on the development of these institutionalized children [See also 81].…”
Section: Physical and Emotional Well-beingmentioning
confidence: 99%
“…Sensory processing and integration have major roles in human development (144). Individuals with FXS have an enhanced sympathetic response to sensory stimuli (145), and the feel of a potty-chair.…”
Section: Other Problemsmentioning
confidence: 99%